The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4103/ijn.ijn_50_18
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological spectrum of xanthogranulomatous pyelonephritis

Abstract: Xanthogranulomatous pyelonephritis (XGP) is an uncommon and distinct type of chronic infective pyelonephritis causing destruction of the kidney, severely affecting the renal function. The perinephric adipose tissue and peritoneum is not uncommonly involved. The study was undertaken to decipher the clinicopathologic spectrum of XGP. Forty cases of XGP were diagnosed on histopathology over a period of 13 years (2005–2017). Relevant clinical details and radiological findings were recorded from the case files. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 26 publications
6
30
0
Order By: Relevance
“…Causes of XGP include chronic renal obstruction, infection, abnormal lipid metabolism, lymphatic obstruction and renal ischemia. Abscess formation (as was observed in our patient), fistula formation (reno--cutaneous, reno-colonic) and profound sepsis are known complications (2).…”
Section: Discussionsupporting
confidence: 76%
“…Causes of XGP include chronic renal obstruction, infection, abnormal lipid metabolism, lymphatic obstruction and renal ischemia. Abscess formation (as was observed in our patient), fistula formation (reno--cutaneous, reno-colonic) and profound sepsis are known complications (2).…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, Immunohistochemistry (IHC) study may be helpful in certain cases. 3,6 CONCLUSION XGP is an uncommon entity associated with urinary tract obstruction and infection. Also, its association with calculus migration into psoas abscess is an unusual complication.…”
Section: Discussionmentioning
confidence: 99%
“…There are three types of XGP (i) diffuse, which is the most common type; (ii) segmental; and (iii) focal, which is limited to the cortex. [5][6][7] Diffuse XGP is associated with massive renal enlargement, peri-pelvic fibrosis, hydronephrosis, lithiasis, and lobulated mass replacing the renal parenchyma. Preoperatively, it is difficult to differentiate, based on clinical and radiological features alone, XGP from other entities like tuberculosis and renal cell carcinoma (RCC).…”
Section: Discussionmentioning
confidence: 99%
“…This author described forty cases of XGP and reported diffuse renal parenchymal involvement in the majority of patients (77.5%) and a high rate (90%) of nephrolithiasis. Furthermore, in their series, these authors identified 5% of coexisting renal cell carcinomas in the same kidney [ 13 ]. In our case series, we found a nephrolithiasis rate of 77.8% and only one patient presented with concomitant renal cell carcinoma (3.7%).…”
Section: Discussionmentioning
confidence: 99%